El mito de la transición pacífica : violencia y política en España (1975-1982) - Baby, Sophie; Fernández Aúz, Tomás; Eguibar, Beatriz; Baby, Sophie (Tres Cantos, Madrid, España : Akal, 2018)
The existence of political violence poses, in every society, a series of challenges that we know well: in the first place, violent action and its containment -be it in dictatorship or already in democracy-, but also issues of memory and national reconciliation, of the role of the law and state violence, of the political role of the victims; many issues that can be addressed in an unprecedented framework-the transition-until the appearance of this magnificent book. "The myth of peaceful transition" is a revealing and pioneering analysis both of the political violence that shook Spain during the transition and of the way in which said violence conditioned and marked the future of the young Spanish democracy.
Includes bibliographical references and index.
Online resource; title from ePub title page (Digitalia, viewed April 25, 2019)
Keywords: Spain -- Politics and government -- 1975-1982.; Political violence -- Spain -- 20th century; Spain -- History -- 20th century; Political persecution -- Spain -- 20th century; Terrorism -- Spain -- 20th century; Electronic books